Release of superoxide and change in morphology by neutrophils in response to phorbol esters: antagonism by inhibitors of calcium-binding proteins (The Rockefeller University Press, 1985)
The ability of phorbol derivatives to function as stimulating agents for superoxide (O2-) release by guinea pig neutrophils has been evaluated and compared to the known ability of each compound to activate protein kinase C. Those that activate the kinase also stimulate O2- release, while those that are inactive with respect to the kinase have no effect on O2- release. The same correlation was observed with respect to the ability of phorbol esters to induce morphological changes in neutrophils, i.e., vesiculation and reduction in granule content. Certain phenothiazines and naphthalene sulfonamides that are known antagonists of calcium-binding proteins blocked both phorbol ester-induced O2- release and morphological changes in these cells.